Demystifying and defending diversity, equity, and inclusion - Cochran Geraldine (EPJ Web of Conferences, 2024)
The constructs of diversity, equity, and inclusion are complex and the DEI movement evokes a variety of strikingly different feelings and responses. One of the challenges to diversity, equity, and inclusion initiatives is that people often have very different views on these endeavors. In this short paper, I offer a concise, global perspective on the conceptualization of diversity, equity, and inclusion that might provide a method for communicating across differences. Though the DEI movement, and associated movements such as the DEI and belongingness movement and the DEI and access movements are important, the length of this paper does not allow for a discussion of these topics. I conclude this paper with a defense of diversity, equity, and inclusion and a discussion of implications for the physics community.